Safety and immunogenicity of a bivalent norovirus vaccine candidate in infants from 6 weeks to 5 months of age: A phase 2, randomized, double-blind trial - Xavier Sáez-Llorens; Rodrigo deAntonio; Eduardo López-Medina; Pío López; Taisei Masuda; Paul M Mendelman; Jim Sherwood; Frank Baehner; Astrid Borkowski (Human Vaccines & Immunotherapeutics)
As infants suffer significant morbidity and mortality due to norovirus-related acute gastroenteritis (AGE), we assessed four formulations of the bivalent virus-like particle (VLP) vaccine candidate (HIL-214) in Panamanian and Colombian infants. 360 infants aged 6 weeks to 5 months were randomly allocated to 8 groups to receive three doses of HIL-214 or two doses of HIL-214 and one dose of placebo (Days 1, 56 and 112), where HIL-214 doses contained 15/15, 15/50, 50/50 or 50/150 μg of GI.1/GII.4c genotype VLPs and 0.5 mg Al(OH)3. Solicited injection-site and systemic adverse events (AE) were collected within 7 days after each dose, unsolicited AEs were collected within 28 days after each, and serious AEs throughout the study. Pan-Ig and histoblood group antigen-blocking antibodies (HBGA) were measured on Days 1, 56, 84, and 140. All formulations were well-tolerated causing mainly mild-to-moderate transient solicited AEs, most frequently local pain and irritability/fussiness, but no vaccine-related serious AEs. Two doses of each formulation induced high titers of high avidity Pan-Ig and also HBGA antibodies; a third dose increased titers against both antigens and the avidity of Pan-Ig antibodies against GII.4c but not against GI.1. Two and three doses of HIL-214 were well-tolerated and induced potent immune responses at 4–6 months of age supporting further clinical assessment to protect against norovirus-related AGE.